An appraisal of islamic banking movement in Nigeria (2006)
The study intends to expose the various moves made by Nigerian Muslims aimed at living by the Shari'ah in their financial transactions. In doing justices to it, the study reviews the historical development of banking services in the country and also the Islamic stand on Riba (interest) and Garar (speculation). It also examines some judicial cases aimed at exposing the attachment of Muslims to Islamic financial system and moves at realizing it. The various moves aimed at Islamising the Nigerian financial system was also traced and recommendations preferred towards improving the Islamic banking climate in Nigeria.